2011
DOI: 10.1007/978-3-642-23059-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Automated Error Correction of Business Process Models

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…Unsound models can be repaired to become sound by simulated annealing [16], though fitness to a given log is not preserved. Non-fitting models can be repaired to become fitting by adding subprocesses [14], though soundness is not guaranteed.…”
Section: Related Workmentioning
confidence: 99%
“…Unsound models can be repaired to become sound by simulated annealing [16], though fitness to a given log is not preserved. Non-fitting models can be repaired to become fitting by adding subprocesses [14], though soundness is not guaranteed.…”
Section: Related Workmentioning
confidence: 99%
“…The idea is to use genetic algorithms such as simulated annealing [24] to create perturbations on the current process instance in order to rectify its execution and thus avoid a fault from eventually occurring. Our previous application of simulated annealing to the problem of automatically correcting business process models [8] has shown that such perturbations can be obtained very efficiently. The challenge stands in properly defining the objective functions so as to create meaningful perturbations.…”
Section: Resultsmentioning
confidence: 99%
“…al. [11]. Their approach considers three dimensions: the structural distance, behavioral distance and 'badness' of a solution w.r.t.…”
Section: Related Workmentioning
confidence: 99%